Problematic online behaviors and their early patterns of co-occurrence in young adults: insights from directed and undirected networks - Błoch, Marta; Misiak, Błażej (Frontiers in Psychiatry, 2025)
IntroductionThe study aimed to identify early patterns of clustering within problematic online behaviors (POBs), their dynamics, and associations with several domains of psychopathology in young adults without a history of psychiatric treatment.MethodsParticipants (n = 1441, aged 29.5 ± 6.3 years, 51.4% females) completed self-report measures recording the level of various POBs and several domains of psychopathology. Various approaches were used to analyze the data, including a principal component analysis together with the analysis of partial correlation networks (undirected associations) and Bayesian networks (directed associations).ResultsThree distinct communities of variables were identified, including two communities of POBs (the first one: problematic use of social networking, problematic online shopping, and cyberchondria; the second one: problematic online gaming and gambling, cybersex) and one community of psychopathology. However, correlations between specific POBs were small to moderate. Problematic use of social networking sites, obsessive-compulsive disorder (OCD) symptoms, and problematic online gaming were found to be the bridge nodes. However, OCD symptoms were most likely to predict other POBs (all POBs except for cybersex). In turn, problematic use of social networking sites predicted the greatest number of other POBs (cyberchondria, gaming, and gambling).DiscussionThese findings suggest that POBs tend to cluster into specific comorbidity patterns while remaining distinct entities. The symptoms of OCD are most likely to trigger the occurrence of POBs. Among POBs, problematic use of social networking sites might be most likely to predict the emergence of other POBs.